Flexicurity in the European Union: flexibility for outsiders, security for insiders - Van Vliet, Olaf; Nijboer, Henk (Munich, 2012)
"Flexicurity is at the heart of European policy debates. Its aim is to overcome the tensions between labour market flexibility on the one hand, and the provision of social security for workers on the other hand. To date, there is little insight into whether flexicurity policies have been adopted across the European Union. Therefore, the aim of this paper is to analyse to what extent labour market policies have been reformed along the lines of the flexicurity concept across 18 European countries over the period 1985-2008. Focusing on the main axes of the flexicurity concept, new datasets are used to examine changes in employment protection legislation, unemployment benefits and active labour market policies. Data on the strictness of employment regulation indicate that reforms have been influenced by labour market insiders,since the level of flexibility has been increased more for temporary employment, the labour market outsiders, than for regular employment, the insiders. Although gross unemployment replacement rates suggest that unemployment benefits have become more generous, net replacement rates indicate that the level of income security from benefits actually has been decreased. Moreover, data illustrate that larger shares of European labour forces have temporary contracts. As such, the gap between insiders and outsiders on the labour market has been increased. This development is contrary to the goals of the European Commission."